2008
DOI: 10.3746/jkfn.2008.37.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Chrysanthemum indicum L. Flower Tea in Relation to the Number of Pan-firing

Abstract: Quality characteristics of Chrysanthemum indicum L. flower tea were investigated with the number of pan-firing. Total nitrogen, tannin and caffeine contents of tea were increased as the number of pan-firing increased, whereas chlorophyll and total amino acid (AA) contents were decreased. TAA content was in the range of 5,226~6,561 mg% with the number of pan-firing. The content of caffeine and chlorophyll was not changed with the number of pan-firing. As the number of pan-firing increased, total polyphenol, fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…덖음이란 물기가 조금 있는 약재나 곡식에 물을 더하지 않고 타지 않을 정도로 볶아서 익히는 과정으로 차의 제조 과정 중에서는 살청(殺淸)과정에 해당된다 (22). 침출차의 제조에 있어서 덖음 처리는 식품의 화학적 성분 조성, 물리적 성질, 그리고 색깔, 향기, 조직감과 같은 관능적 품질요소에 영향을 미치는 것으로 보고되고 있다 (12,(22)(23)(24). Yoon과 Kim(25) 은 보리의 덖음 조건이 보리차의 점도 및 맛과 냄새 등 관능 적 특성에 대한 영향을 연구하였으며, Ha 등(26)과 Lee 등 (27) (30).…”
unclassified
“…덖음이란 물기가 조금 있는 약재나 곡식에 물을 더하지 않고 타지 않을 정도로 볶아서 익히는 과정으로 차의 제조 과정 중에서는 살청(殺淸)과정에 해당된다 (22). 침출차의 제조에 있어서 덖음 처리는 식품의 화학적 성분 조성, 물리적 성질, 그리고 색깔, 향기, 조직감과 같은 관능적 품질요소에 영향을 미치는 것으로 보고되고 있다 (12,(22)(23)(24). Yoon과 Kim(25) 은 보리의 덖음 조건이 보리차의 점도 및 맛과 냄새 등 관능 적 특성에 대한 영향을 연구하였으며, Ha 등(26)과 Lee 등 (27) (30).…”
unclassified
“…Polyphenol compounds can be converted to low molecular weight compounds by heating, and new phenolic compounds can be produced (Woo et al 2006). Moreover, many studies have reported that the antioxidant activity of flavonoids and tannins increases when plant materials are heated, such as chicory (Hong et al 1998), Polygonatum odoratum tea (Ryu et al 1997), chrysanthemum indicum L. (Yu et al 2008), and horseweed (Woo et al 2009). …”
Section: Three-dimensional (3d) Response Surface Results For the Thrementioning
confidence: 96%
“…볶음처리는 건강기능성이 높은 유용성분을 생성할 뿐만 아니라 향미성분도 증가시킴으로써 차 생산에 많이 이용되고 있다. 볶음차의 항산화 및 항돌연변이 기능성 에 대한 보고로는 오가피차 (10), 율무차 (11), 둥글레차 (12), 발아 벼 차 (13), 옻나무 열수추출물 (14), 동백잎차 (15), 녹차 (16), 감국 꽃차 (17) Table 4. Changes in the free amino acid contents of the dried radish before and after pressurized roasting (mg/100 g) Oxidative stress was induced by superoxide, nitric oxide or peroxynitrite which was generated in the treatment of pyrogallol, sodium nitroprusside (SNP) or 3-morpholinosydnonimine (SIN-1), respectively.…”
Section: 서 론unclassified